The 1958-62 Chinese Famine and Its Impact on Ethnic Minorities - Bianco, Lucien (East/West, 2021)
China underwent its most murderous famine between 1958 and 1962. Although a demographic transition from the countryside to the cities was in its early stage and gross domestic product (GDP) per capita was among the lowest in the world, objective conditions were far less decisive than Chinese Communist Party (CCP) policies in bringing about the famine. A development strategy copied on the Soviet model favoured quick industrialization at the expense of rural dwellers. Such novelties as people’s communes, communal canteens, and backyard furnaces further aggravated the famine. Though ethnic minorities represented only 6 percent of China’s population, compared to forty-seven percent in the Soviet Union, Soviet nationality policies heavily influenced those of China. Initially mild, especially for Tibetans, Chinese nationality policies became more authoritarian with the advent of the Great Leap Forward in 1958. Qinghai Tibetans resisted the closure of many monasteries; then the same policies, and famine itself, caused a more important rebellion in 1959 in Xizang (Tibet). Repression and the flight of the Dalai Lama to northern India coincided with the end of Tibet’s special status in China.Internal colonialism did not, however, aggravate the impact of famine on national minorities in China. Their rate of population growth between the first two censuses (1953 and 1982) exceeded that of Han Chinese. Among the provinces most severely affected by famine, only Qinghai was largely inhabited by ethnic minorities. Within Qinghai the same pattern prevailed as in Han populated provinces: the highest toll in famine deaths was concentrated in easily accessible grain surplus areas. The overwhelming majority of victims of the Chinese famine were Han peasants. At most, 5 percent were members of ethnic minorities, compared to eighty percent of victims in the Soviet Union in the period between 1930 and 1933.